Myricetin Increases Hepatic Peroxisome Proliferator-Activated Receptor α Protein Expression and Decreases Plasma Lipids and Adiposity in Rats. (8th March 2012) - Chang, Chia Ju; Tzeng, Thing-Fong; Liou, Shorong-Shii; Chang, Yuan-Shiun; Liu, I-Min
Abstract : The aim of this study was to investigate the antiobesity and antihyperlipidaemic effects of myricetin. Myricetin exhibited a significant concentration-dependent decrease in the intracellular accumulation of triglyceride in 3T3-L1 adipocytes. The high-fat diet (HFD)-fed rats were dosed orally with myricetin or fenofibrate, once daily for eight weeks. Myricetin (300 mg kg −1 per day) displayed similar characteristics to fenofibrate (100 mg kg −1 per day) in reducing lowered body weight (BW) gain, visceral fat-pad weights and plasma lipid levels of HFD-fed rats. Myricetin also reduced the hepatic triglyceride and cholesterol contents, as well as lowered hepatic lipid droplets accumulation and epididymal adipocyte size in HFD-fed rats. Myricetin and fenofibrate reversed the HFD-induced down-regulation of the hepatic peroxisome proliferator activated receptor (PPAR) α . HFD-induced decreases of the hepatic protein level of acyl-CoA oxidase and cytochrome P450 isoform 4A1 were up-regulated by myricetin and fenofibrate. The elevated expressions of hepatic sterol regulatory element binding proteins (SREBPs) of HFD-fed rats were lowered by myricetin and fenofibrate. These results suggest that myricetin suppressed BW gain and body fat accumulation by increasing the fatty acid oxidation, which was likely mediated via up-regulation of PPAR α and down-regulation of SREBP expressions in the liver of HFD-fed rats.